Cnidom in Ceriantharia (Cnidaria, Anthozoa): new findings in the composition and micrometric variations of cnidocysts - Garese, Agustin (2023)
Background: Like all cnidarians, the subclass Ceriantharia (Cnidaria, Anthozoa) is known for producing cnidocysts, which mainly serve for prey immobilization, predator defense, and locomotion. Aim: The present study aimed to understand the variability of the cnidom, i.e., the inventory of all cnidocyst types, in the ceriantharians (tube anemones) Ceriantheomorphe brasiliensis (10 individuals) and Cerianthus sp. (seven individuals). Methods: In each individual, 30 intact cnidocysts of each identified type were measured in the following parts of tube anemones: marginal tentacles (four from each individual), labial tentacles (four from each individual), column, actinopharynx and metamesenteries. Each of these structures was divided into three levels (high, middle, and low) and the cnidom was analyzed. Statistical descriptive parameters (mean, standard deviation, minimum and maximum) of the sizes of all types of cnidocysts were calculated. The normality of the data for cnidocyst length was assessed using a Shapiro-Wilk test (a = 0.05). Based on the acceptance or rejection of the normality, either linear models or generalized linear models were used to evaluate variations in cnidocyst lengths. The normality of the cnidocyst length was tested by Shapiro-Wilk, and due to its rejection, generalized linear mixed models were applied to test the cnidocyst lengths variations. Results: The analysis of Ceriantheomorphe brasiliensis revealed 23 categories of cnidocysts, thereby expanding the understanding of its cnidome. The cnidoms of Ceriantheomorphe brasiliensis and Cerianthus sp. presented intraspecific variations, both qualitatively and in the lengths of cnidocysts. The cnidoms of the two species studied also showed qualitative intra-individual variations between different levels (high, middle, low) within each structure of the tube anemone (tentacles, actinopharynx, column and metamesenteries). Some cnidocyst types, such as atrichs from the column of C. brasiliensis, presented a length gradient along the column, from larger lengths at the “low” level to smaller lengths at the “high” level. Conclusions: The cnidom of a tube anemone could be better described if samples are taken at different levels of the structures, as observed in C. brasiliensis. In addition, we can conclude that the cnidocyst lengths of both C. brasiliensis and Cerianthus sp. present intraspecific variation, which is coincident with that observed in actiniarian sea anemones. Moreover, as main conclusion, this work also proved that individuals of tube anemone species could present qualitative intra-structure variations in both the cnidom and cnidocyst lengths. This characteristic appears as an exception in cnidom variations, and has so far not been recorded even in the most studied actiniarian sea anemones. Finally, the intra-structure cnidocyst variations could reveal different functions of the different levels of a particular body part of the organisms.